The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1415-47572014000100008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of bocachico Prochilodus magdalenae (Pisces, Prochilodontidae) in the Magdalena River basin and its tributaries, Colombia

Abstract: Prochilodus magdalenae is an endemic freshwater fish that occurs in the Magdalena, Sinú and Atrato hydrographic basins. It has an important economic role and is a food resource for the artisanal fishing communities. Its socioeconomic importance contrasts with the current status of its fisheries, where stocks are being depleted. Considering its importance and lack of information on its genetic structure, we used seven microsatellite markers to assess the genetic structure of wild populations of P. magdalenae. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
4
18
4
Order By: Relevance
“…The same pattern was obtained for other species of this genus in the Magdalenae River for P. magdalenae (H E = 0.877)(Berdugo and Barandica 2014) and in the São Francisco River for P. argenteus (H E = 0.605-0.785)(Barbosa et al 2006;Hatanaka et al 2006;Barbosa et al 2008;Sanches et al 2012) and P. costatus (0.448-0.660) (Carvalho-Costa et al…”
supporting
confidence: 72%
See 4 more Smart Citations
“…The same pattern was obtained for other species of this genus in the Magdalenae River for P. magdalenae (H E = 0.877)(Berdugo and Barandica 2014) and in the São Francisco River for P. argenteus (H E = 0.605-0.785)(Barbosa et al 2006;Hatanaka et al 2006;Barbosa et al 2008;Sanches et al 2012) and P. costatus (0.448-0.660) (Carvalho-Costa et al…”
supporting
confidence: 72%
“…In addition, large effective population sizes also increase the rate of allelic Rev Fish Biol Fisheries recombination (Agostinho et al 2003;Ferreira et al 2015). Prochilodus lineatus samples analyzed in this study showed high genetic diversity levels comparable to other migratory freshwater fish (Matsumoto and Hilsdorf 2009;Santos et al 2007;Berdugo and Barandica 2014). Microsatellite analysis suggested relatively high levels of genetic diversity (H E = 0.803-0.874 and N A = 11.42-20.42 alleles per locus), higher than the average estimated for freshwater fish (H E = 0.54 and N A = 9.1 alleles per locus) (Dewoody and Avise 2000), and similar to those previously reported for other Neotropical migratory fish species (Calcagnotto et al 2001;Barroso et al 2003Barroso et al , 2005Morelli et al 2007;Matsumoto and Hilsdorf 2009).…”
Section: Genetic Diversity and Demographic Analysismentioning
confidence: 69%
See 3 more Smart Citations